Pemberian Upah Bagi Jasa Penulis Bayangan (Ghostwriter) Perspektif Fikih Muamalah - Ovita Sari (Fakultas Syariah Institut Agama Islam Negeri Palu, 2023)
Giving wages for ghostwriters’ services basically meets the requirements of sighat and wages in muamalat. However, the existence of ghostwriter services is actually contrary to the academic code of ethics. And it also has a negative impact on the development of the quality of education. The purpose of this research is to find out the concept of wages according to Islamic law and to find out the views of Islamic law on giving wages to ghostwriters. This study uses the library method by finding sources of information through previous research studies. The implications of this research are expected to be able to provide a bit of an overview regarding the remuneration of ghostwriters. The study results show that the form of the contract and the wage system used by the ghostwriter services fulfill the sighat and wage requirements in fiqh muamalah. However, the use of ghostwriting services actually violates the academic code of ethics and has negative implications for the quality of education, and in the view of Islamic law the existence of shadow writing services is in fact considered unlawful because there is an element of fraud in it.